Giving Exclusive ASI to Samin Community in Japanese Central Desa Margomulyo Kecamatan Margomulyo Bojonegoro District - Andin Ajeng Rahmawati; Nurwijayanti Nurwijayanti; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
ASI is the best nutrition for babies that must be given until the age of 2 years. But at 6 months the baby needs to get additional food. Complementary food for breast milk or solids starts to be given at the age of 6 months because the digestive process of babies who have started is perfect. ASI companion needs to be done to fulfill the baby's nutrition. The Samin community has its own local knowledge regarding infant feeding. The provision of complementary breastfeeding is associated with knowledge of pusak pusak which is the standard for the Samin community in providing complementary food for babies, the dizziness occurs at the age of babies reaching 5 to 7 days, so the baby's belly button will fall or fall and this event is called the pusak puser. The purpose of this study is to know and describe exclusive breastfeeding for mothers who have infants under 2 years of age and describe the practices of mothers in exclusive breastfeeding and supplementary food for infants in the Samin community. The research design used was qualitative ethnography with a phenomenology approach. Data collection uses in-depth interview techniques with semi-structured questions. The sampling technique in this study used purposive sampling with a sample of 15 informants from 30 informants. The results of the study show that local beliefs and culture influence exclusive breastfeeding and will have less impact on both breastfeeding mothers and infants. In the process of implementing this research are influenced by several factors including internal factors and external factors. Internal factors include maternal characteristics (age, parity, education, work), knowledge, trust while external factors include support from health workers (counseling, policies, recording and reporting systems) and family support